2022
DOI: 10.1111/mms.12951
|View full text |Cite
|
Sign up to set email alerts
|

Extracting foraging behavior from passive acoustic monitoring data to better understand harbor porpoise (Phocoena phocoena) foraging habitat use

Abstract: For odontocetes, passive acoustic monitoring (PAM) can be used to differentiate between occurrence and foraging through analysis of click characteristics. Feeding buzzes and navigation/searching echolocation clicks of harbor porpoise (Phocoena phocoena) were differentiated within C‐POD data from northwest Ireland between 2009 and 2017. The spatiotemporal distribution of foraging behavior was investigated using generalized additive modelling, at multiple temporal scales. Both the presence/absence of buzzes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Chinook salmon moved between shallow water column depths during the day and deeper depths at night (Figure 3), which represents the opposite diel pattern of many marine fishes (Brierley, 2014; Hays, 2003). Salmon may be using daylight in surface waters for foraging or navigation and/or retreating deeper at night to avoid nocturnal, surface‐oriented marine predators (Byron & Burke, 2014; Tanaka et al, 2000; Todd et al, 2022; Wilson et al, 2014). Two tagging studies also found that the deepest Chinook salmon dives occurred at night; however, other studies have observed opposite and variable patterns (Arostegui et al, 2017; Courtney et al, 2019; Hinke, Foley et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Chinook salmon moved between shallow water column depths during the day and deeper depths at night (Figure 3), which represents the opposite diel pattern of many marine fishes (Brierley, 2014; Hays, 2003). Salmon may be using daylight in surface waters for foraging or navigation and/or retreating deeper at night to avoid nocturnal, surface‐oriented marine predators (Byron & Burke, 2014; Tanaka et al, 2000; Todd et al, 2022; Wilson et al, 2014). Two tagging studies also found that the deepest Chinook salmon dives occurred at night; however, other studies have observed opposite and variable patterns (Arostegui et al, 2017; Courtney et al, 2019; Hinke, Foley et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of dolphin acoustic activity have suggested that several species echolocate at a lower rate during daylight hours, possibly relating to patterns in foraging activity or increased use of visual cues during this period (Soldevilla et al 2010a(Soldevilla et al , 2010bWang et al 2015). Previous studies of harbour porpoises off the west coast of Scotland (Carlström 2005), Dogger Bank (Todd et al 2009), and off north-western Ireland (Todd et al 2022) have demonstrated higher encounter rates at night containing higher click rates with minimum interclick intervals of < 10 ms (ms), indicative of increased foraging activities. The findings of our study suggest that harbour porpoises are either echolocating less in the development site at night, possibly in response to the construction and operation of the wind turbines, or that they have shifted their diel use at the site, perhaps associated with increased foraging opportunities granted by a possible reef-effect or reduction in fishing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Foraging buzzes are presumed prey capture attempts with a typical ICI of less than 10 ms (DeRuiter et al, 2009 ; Miller, 2010 ; Verfuß et al, 2009 ). Gaussian mixture models were used to categorize echolocation clicks based on their ICI (Berges et al, 2019 ; Pirotta, Brookes, et al, 2014 ; Pirotta, Thompson, et al, 2014 ; Todd et al, 2022 ). This method classifies log‐transformed ICIs to identify patterns of echolocation clicks.…”
Section: Methodsmentioning
confidence: 99%
“…Over the years PAM technology has greatly advanced the field of cetacean ecology, allowing a cost‐effective alternative to extensive visual surveys that are not reliant on daylight hours, favorable weather conditions, and availability of observers. Passive acoustic monitoring of cetaceans has resulted in temporally high‐resolution data providing us with insights into population size and abundance (Amundin et al, 2022 ; Marques et al, 2013 ), habitat use (Fleming et al, 2018 ; Palmer et al, 2019 ), and behavior (Malinka et al, 2021 ; Pirotta, Thompson, et al, 2014 ; Todd et al, 2022 ) for many species. Such technology is also fundamental for long‐term monitoring, particularly with the increase in coastal developments and potential disturbance from construction, marine renewable devices, shipping, and fisheries (e.g., Fernandez‐Betelu et al, 2022 ; Omeyer et al, 2020 ; Ramesh et al, 2021 ; Todd et al, 2020 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%